2002
DOI: 10.1002/1099-0682(20022)2002:2<439::aid-ejic439>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Methyl- and Acetylpalladium(II) Complexes Containing a P,N,O Tridentate Hydrazone Ligand

Abstract: The hydrazone ligand 2‐(diphenylphosphanyl)benzaldehyde benzoylhydrazone (HPNO) forms the methyl PdII complex [Pd(HPN)(Me)Cl] (1) in high yield when treated with [(COD)Pd(Me)Cl] in dichloromethane or diethyl ether at room temperature. In complex 1, the ligand remains neutral and is P,N bidentate. The deprotonation of the ligand by Et3N affords [Pd(PNO)(Me)] (2), in which the anionic ligand is P,N,O tridentate. When 1 is treated with AgCF3SO3, the cationic complex [Pd(HPNO)(Me)]+[CF3SO3]− (3) is formed; here th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The molecular structure of the complex is shown in Figure 3a. As the ligand itself did not isomerize under the same conditions, the Ru II (2) 166.53 (5) 92.23(4) 98.08 (3) 88.81(6) P(1)-Ru(1)-P (2) 98.30 (5) 97.21(4) 172.83 (2) 177 The Ru center has a distorted octahedral coordination geometry with two PPh 3 ligands located in mutual cis positions and two Clligands in mutual trans positions; thus, the coordination geometry can be assigned as trans(Cl,Cl).…”
Section: Syntheses and Crystal Structures Of [Rucl 2 (Pph 3 ) 2 (Hl)]mentioning
confidence: 98%
See 1 more Smart Citation
“…The molecular structure of the complex is shown in Figure 3a. As the ligand itself did not isomerize under the same conditions, the Ru II (2) 166.53 (5) 92.23(4) 98.08 (3) 88.81(6) P(1)-Ru(1)-P (2) 98.30 (5) 97.21(4) 172.83 (2) 177 The Ru center has a distorted octahedral coordination geometry with two PPh 3 ligands located in mutual cis positions and two Clligands in mutual trans positions; thus, the coordination geometry can be assigned as trans(Cl,Cl).…”
Section: Syntheses and Crystal Structures Of [Rucl 2 (Pph 3 ) 2 (Hl)]mentioning
confidence: 98%
“…[1][2][3] A wide variety and number of transition-metal complexes bearing such N-and C-substituted hydrazones have been reported, and their possible uses in advanced functional materials have been examined. They have two possible configurational isomers, E and Z, in relation to the orientation of the substituents attached to the C=N moiety.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the coordination chemistry of tridentate PNO ligands that combine both hard and soft donor atoms have attracted considerable interest. [120][121][122] Peng et al 123 introduced the tridentate PNO receptor and reported a new rhodamine hydrazone probe 89 (Fig. 31, right) exhibiting highly improved sensing properties for Pd 2+ compared with the probe in their previous study.…”
Section: Based On Rhodamine Spirolactam Systemmentioning
confidence: 99%
“…22 Various metal complexes of hydrazine-derived ligands have been reported with fascinating functionalities and bonding modes, potential catalysts, biologically active agents and single molecule magnets. [23][24][25][26][27][28] In acylhydrazone ligands, deprotonation of the -NH group is readily achieved, mediated by base or metal while forming complexes and is responsible for various serendipitous bonding modes. 29 Among all the complexes which we report here, metal-mediated deprotonation of -NH group is observed because it is achieved even without using any base.…”
Section: Introductionmentioning
confidence: 99%